1993
DOI: 10.3758/bf03334950
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of color harmony

Abstract: Twenty-one subjects rated a random sequence of 144 color pairs on a categorical scale ranging from 1 (harmonizing) to 7 (clashing). Another group of 35 subjects rated each individual color on a set of semantic differential scales. The colors were also scaled objectively in terms of Munsell measures for hue, chroma, and value. The color harmony ratings were analyzed by using multidimensional scaling and invoking a weighted individual-differences Euclidean distance model. A two-dimensional solution accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Polzella & Montgomery [20] found that the more harmonious combinations involved colors of similar brightness or similar hue, which matches afore mentioned principles. The parameter of saturation seems to have no effect on color harmony.…”
Section: Modeling Color Harmonysupporting
confidence: 73%
See 3 more Smart Citations
“…Polzella & Montgomery [20] found that the more harmonious combinations involved colors of similar brightness or similar hue, which matches afore mentioned principles. The parameter of saturation seems to have no effect on color harmony.…”
Section: Modeling Color Harmonysupporting
confidence: 73%
“…The worst rated combinations on the other hand showed little or no difference. This conclusion was later found not to be generally applicable [20]. Another study [25] focused also on the combination of foreground and background color, but in the context of legibility, which describes the visual clarity of text -in short legibility is how well one can see the letters [1].…”
Section: Modeling Color Harmonymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the details of their theories differed considerably and empirical tests were infrequent and conflicting (Ou & Luo, 2006). More recently, researchers have presented participants with pairs of color patches and collected ratings of “harmoniousness” or “clashing.” The presented pairs were typically based on changing one aspect of color at a time (e.g., brightness or hue) and the empirical results were often mixed or conflicting (e.g., Chuang & Ou, 2001; Polzella & Montgomery, 1993; Ou & Luo, 2006).…”
Section: Testing Preferences For Color Combinations In Aesthetic Selfmentioning
confidence: 99%